2019
DOI: 10.1113/jp277312
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating microparticles in streptozotocin‐induced diabetes propagate inflammation contributing to microvascular dysfunction

Abstract: Key points Circulating microparticles (MPs) are elevated in many cardiovascular diseases and have been considered as biomarkers of disease prognosis; however, current knowledge of MP functions has been mainly derived from in vitro studies and their precise impact on vascular inflammation and disease progression remains obscure. Using a diabetic rat model, we identified a >130‐fold increase in MPs in plasma of diabetic rats compared to normal rats, the majority of which circulated as aggregates, expressing mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 62 publications
0
16
0
2
Order By: Relevance
“…Соответственно, в условиях гипергликемии и инсулинорезистентности эндотелиальная дисфункция формируется быстро и определяет тяжесть других осложнений СД2. На модели стрептозотоцитового диабета крыс было выявлено многократное увеличение эндогенных микрочастиц размером от 220 нм до 1300 нм (разновидность ВВ) у диабетических крыс по сравнению с контролем с гиперэкспрессией поверхностного фосфатидилсерина [36]. Диабетические микрочастицы, находясь в циркуляции, формировали агрегаты и обуславливали повышенную адгезию лейкоцитов и повышенную чувствительность эндотелиоцитов к воспалительным стимулам [36].…”
Section: варианты взаимодействия экзосом с клеткой без интернализацииunclassified
See 1 more Smart Citation
“…Соответственно, в условиях гипергликемии и инсулинорезистентности эндотелиальная дисфункция формируется быстро и определяет тяжесть других осложнений СД2. На модели стрептозотоцитового диабета крыс было выявлено многократное увеличение эндогенных микрочастиц размером от 220 нм до 1300 нм (разновидность ВВ) у диабетических крыс по сравнению с контролем с гиперэкспрессией поверхностного фосфатидилсерина [36]. Диабетические микрочастицы, находясь в циркуляции, формировали агрегаты и обуславливали повышенную адгезию лейкоцитов и повышенную чувствительность эндотелиоцитов к воспалительным стимулам [36].…”
Section: варианты взаимодействия экзосом с клеткой без интернализацииunclassified
“…На модели стрептозотоцитового диабета крыс было выявлено многократное увеличение эндогенных микрочастиц размером от 220 нм до 1300 нм (разновидность ВВ) у диабетических крыс по сравнению с контролем с гиперэкспрессией поверхностного фосфатидилсерина [36]. Диабетические микрочастицы, находясь в циркуляции, формировали агрегаты и обуславливали повышенную адгезию лейкоцитов и повышенную чувствительность эндотелиоцитов к воспалительным стимулам [36]. Аналогичные данные получены и в экспериментах моделирования инсулинорезистентности in vitro [37].…”
Section: варианты взаимодействия экзосом с клеткой без интернализацииunclassified
“…Correlation and regression analysis indicated significant positive correlation between endothelial lEVs and HbA1c level, and that endothelial lEVs are independent predictors of endothelial dysfunction (reduced flow-mediated dilation of brachial artery and elevated brachial ankle pulse wave velocity) in diabetic patients, respectively [ 87 ]. Feng et al [ 88 ] and Ishida et al [ 89 ] showed significantly elevated levels of circulating lEVs from endothelial, leukocyte and platelet origins in STZ-induced diabetic rats, compared to non-diabetic rats [ 88 , 89 ].…”
Section: Levs (Mps) and Endothelial Dysfunctionmentioning
confidence: 99%
“…Furthermore, a significant positive correlation between EMPs and glycated hemoglobin (HbA1c) levels was observed, and EMPs were identified as independent predictors of endothelial dysfunction (reduced flow-mediated dilation of brachial artery and elevated brachial ankle pulse wave velocity) in diabetic patients (7). Feng et al (8) and Ishida et al (9) showed significantly elevated levels of circulating MPs from endothelial origin in streptozotocin-induced diabetic rats, compared to non-diabetic rats (8,9).…”
Section: Introductionmentioning
confidence: 99%